2015
DOI: 10.1097/rct.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reducing Field of View on Multidetector Quantitative Computed Tomography Parameters of Airway Wall Thickness in Asthma

Abstract: Objective We reduced the CT-reconstructed field of view (FOV), increasing pixel density across airway structures and reducing partial volume effects, to determine whether this would improve accuracy of airway wall thickness quantification. Methods We performed CT imaging on a lung phantom and 29 subjects. Images were reconstructed at 30, 15, and 10 cm FOV using a medium-smooth kernel. Cross-sectional airway dimensions were compared at each FOV with repeated-measures analysis of variance. Results Phantom me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Improvement in image quality in the lung field plays an important role in diagnosis. Studies reported that U-HRCT can improve nodule images in the lung or bronchi, thereby improving diagnostic confidence [6,20]. It was also reported that when using U-HRCT with a small FOV (100 mm), the lung nodule image quality and diagnostic confidence were improved compared with conventional HRCT with a larger FOV (350 mm) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in image quality in the lung field plays an important role in diagnosis. Studies reported that U-HRCT can improve nodule images in the lung or bronchi, thereby improving diagnostic confidence [6,20]. It was also reported that when using U-HRCT with a small FOV (100 mm), the lung nodule image quality and diagnostic confidence were improved compared with conventional HRCT with a larger FOV (350 mm) [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference between U-HRCT target scans and conventional CT target reconstructions was not statistically significant with regard to the identification of burr sign, vacuole sign, air bronchial sign, and fissure distortion. Sheshadri et al (21) reported that obtaining U-HRCT target scans using a small FOV significantly improved the spatial resolution of images. Our results show that U-HRCT target scans provided better image quality in mixed component ground-glass lung adenocarcinoma ( Figure 5).…”
Section: B C Amentioning
confidence: 99%
“…Most lymph nodes were located in level VI in our study, and small lymph nodes account for the majority of them. For small FOV CT images, the signal-to-noise ratio and spatial resolution have improved (8,(13)(14)(15)(16). ROI was often drawn in the enhancement area in previous studies, and this area did not necessarily represent the entire lymph node.…”
Section: Discussionmentioning
confidence: 99%